MODERN METHODS OF TREATMENT OF LONG-TERM NON-HEALING WOUNDS AND PREVENTION OF GENERALISATION OF INFECTION - Khamdamov, B.Z.; Umarov, B.Ya. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The relevance of the problem of treating long-term non-healing wounds is due not only to medical significance but also to social and economic importance. Long-term non-healing wounds are a heavy burden for both patients and their family members. Due to the presence of pain, infection, loss of function in the affected area, as well as constant financial costs, not only does the quality of life decrease and the number of disabled people increase, but conditions are created for the generalisation of infection, the development of surgical sepsis and the death of the patient. A distinctive feature of the generalisation of infection in patients with long-term non-healing wounds is the presence of a focus on chronic inflammation caused by the infiltration of pro-inflammatory immune cells. Thus, the development of strategies based on the regulation of immune cell functions is a promising approach in regenerative medicine for the treatment of chronic wounds, including diabetic, vascular and pressure ulcers, on the one hand, and the prevention of generalisation of infection, on the other. We summarised different approaches to immunomodulation to improve wound healing and prevent generalised infection.